2017
DOI: 10.1016/j.neuint.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The orphan G protein-coupled receptor GPR139 is activated by the peptides: Adrenocorticotropic hormone (ACTH), α-, and β-melanocyte stimulating hormone (α-MSH, and β-MSH), and the conserved core motif HFRW

Abstract: GPR139 is an orphan G protein-coupled receptor that is expressed primarily in the brain. Not much is known regarding the function of GPR139. Recently we have shown that GPR139 is activated by the amino acids l-tryptophan and l-phenylalanine (EC50 values of 220 μM and 320 μM, respectively), as well as di-peptides comprised of aromatic amino acids. This led us to hypothesize that GPR139 may be activated by peptides. Sequence alignment of the binding cavities of all class A GPCRs, revealed that the binding pocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 46 publications
2
41
3
Order By: Relevance
“…We also demonstrated that L‐Trp and L‐Phe activated GPR139‐dependent mitogen activated protein kinase‐ERK phosphorylation . Recently, Nøhr et al reported that GPR139 can be activated by adrenocorticotropic hormone (ACTH), α‐, and β‐melanocyte stimulating hormone (α‐MSH, and β‐MSH) . However, our recent data do not support that GPR139 is activated by ACTH, α‐MSH, and β‐MSH at physiologically relevant concentrations.…”
Section: Introductioncontrasting
confidence: 70%
See 1 more Smart Citation
“…We also demonstrated that L‐Trp and L‐Phe activated GPR139‐dependent mitogen activated protein kinase‐ERK phosphorylation . Recently, Nøhr et al reported that GPR139 can be activated by adrenocorticotropic hormone (ACTH), α‐, and β‐melanocyte stimulating hormone (α‐MSH, and β‐MSH) . However, our recent data do not support that GPR139 is activated by ACTH, α‐MSH, and β‐MSH at physiologically relevant concentrations.…”
Section: Introductioncontrasting
confidence: 70%
“…1 Recently, Nøhr et al reported that GPR139 can be activated by adrenocorticotropic hormone (ACTH), α-, and β-melanocyte stimulating hormone (α-MSH, and β-MSH). 9 However, our recent data do not support that GPR139 is activated by ACTH, α-MSH, and β-MSH at physiologically relevant concentrations. But we were able to demonstrate an in vitro interaction between GPR139 and the melanocortin receptors (MCRs, also known as melanocyte stimulating hormone receptors), which may be an artifactual result of recombinant expression.…”
Section: Introductioncontrasting
confidence: 61%
“…Interestingly, αMSH was recently reported to activate an orphan G‐coupled receptor, GPR139. Upon overexpression in CHO cells, this orphan receptor was demonstrated to behave like a G q receptor (Nøhr et al , ). It is important to note that αMSH was reported to be 100‐fold less potent agonist of GPR139 in comparison with MC4R, a G s receptor (Nøhr et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Antagonism of GPR139 with JNJ‐63533054 reduced both escalated drinking and hyperalgesia symptoms in alcohol‐dependent rats. The endogenous ligand for GPR139 is unclear at the present time, but may relate to either tryptophan/serotonin signaling (Liu et al, ), adrenocorticotropic hormone (ACTH), and/or melanocyte‐stimulating hormone (Nohr et al, ).…”
Section: Preclinical Findings In Rodent Models Of Alcohol Dependence mentioning
confidence: 99%